Visual arts in retailing - Yahya, Wan Kalthom; Muthusamy, Geetha; Naseri, Roszi Naszariah Nasni; Hasbullah, Nornajihah Nadia (Faculty of Art and Design, 2025)
Visual arts and retail share a profound connection through their focus on aesthetics, emotional resonance, and storytelling. As retail transforms, visual creativity becomes increasingly central to building brand identity, capturing consumer attention, and delivering immersive experiences. In the digital space, high-quality imagery including photography, video content, and graphic design helps brands forge emotional bonds with audiences. Social media, user-generated content, and influencer marketing amplify this visual strategy, enhancing visibility and reinforcing brand recognition. Since digital channels now function as storefronts, cohesive visual presentation is key to a strong online presence. In physical retail environments, creative visual merchandising, immersive design, and interactive technologies like Augmented Reality (AR) enhance the shopper experience, increase engagement, and elevate customer satisfaction. Premium retailers leverage artistic window displays, thematic layouts, and tech-driven installations to stand out. By blending aesthetics, psychological insights, and spatial design, visual arts continue to redefine the shopping journey. Businesses that embrace artistic elements in their branding and customer interactions can build loyalty, differentiate themselves, and drive lasting success.